Infective Endocarditis - Magnusson, Peter; Razmi, Robin (IntechOpen, 2019)
Infective endocarditis is a potentially life-threatening devastating disease. Due to its diagnostic difficulties, definite diagnosis may be delayed. Once diagnosed, the treatment options need careful judgment preferably among team members with specialization in cardiology, imaging, infectious disease, and thoracic surgery. The purpose of this book is to cover various aspects of the management of infectious endocarditis, which may serve as a basis of knowledge that will facilitate implementation of improved, evidenced-based care for this challenging disease.